2017
DOI: 10.1159/000480535
|View full text |Cite
|
Sign up to set email alerts
|

Early Use of Mother's Own Raw Milk, Maternal Satisfaction, and Breastfeeding Continuation in Hospitalised Neonates: A Prospective Cohort Study

Abstract: Background: Despite the critical importance of breast milk for preterm and sick neonates, there is no consensus regarding the use of raw mother's own milk (MOM) in neonatal units. Objectives: This study aimed to describe the use of raw MOM in hospitalised neonates before day 7 (early use), and to investigate: (i) related factors, (ii) maternal satisfaction, and (iii) the association with breastfeeding continuation. Methods: This prospective cohort included 516 neonates intended to be breastfed in 2 French neon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Feeding with human breast milk rather than formula is the simplest family-centred, valued and effective immunoprotective strategy [49, 50]. Donor breast milk may be beneficial for infants whose mothers cannot provide expressed breast milk, but the cost-effectiveness of this policy remains to be established in some contexts and settings.…”
Section: Resultsmentioning
confidence: 99%
“…Feeding with human breast milk rather than formula is the simplest family-centred, valued and effective immunoprotective strategy [49, 50]. Donor breast milk may be beneficial for infants whose mothers cannot provide expressed breast milk, but the cost-effectiveness of this policy remains to be established in some contexts and settings.…”
Section: Resultsmentioning
confidence: 99%
“…Dritsakou et al suggested that feeding VLBW infants predominantly with the mother's own raw milk results in better neonatal outcomes such as higher body length and head circumference at discharge [69]. In addition, a prospective cohort study conducted with VLBW infants fed exclusively with HM demonstrated an association between the early use of the mother's own raw milk and continued breastfeeding at discharge (OR 2.92; 95% CI [1.94–4.40]), and after 6 months (OR 2.70; 95% CI [1.21–6.03]) [70].…”
Section: Discussionmentioning
confidence: 99%
“…Since any disturbance of the postnatal bonding period adversely affects motherhood, including lactation and breastfeeding, all measures supporting early skin-to-skin contact and avoiding division of the mother-infant dyad are welcome [27]. Lowering the incidence of neonatal respiratory morbidity helps preserve the dyad and thus increase the likelihood of successful lactation and breast-feeding [28]. The key hormone in mammalian parenting and social development is oxytocin [29].…”
Section: Discussionmentioning
confidence: 99%